Design and optimization of 3D-bioprinted scaffold framework based on a new natural polymeric bioink. (17th August 2021) - Dorati, Rossella; Chiesa, Enrica; Riva, Federica; Modena, Tiziana; Marconi, Stefania; Auricchio, Ferdinando; Genta, Ida; Conti, Bice
Abstract: Objectives: This aimed at the design and production of engineered 3D scaffold prototypes using a natural polymeric bioink made of chitosan and poly-γ-glutamic acid with a specific focus on 3D-bioprinting process and on 3D framework geometry. Methods: Prototypes were produced using a 3D bioprinter exploiting layer-by-layer deposition technology. The 3D scaffold prototypes were fully characterized concerning pore size and size distribution, stability in different experimental conditions, swelling capability, and human dermal fibroblasts viability. Key findings: Hexagonal framework combined with biopaper allowed stabilizing the 3-layers structure during process manufacturing and during incubation in cell culture conditions. The stability of 3-layers structure was well preserved for 48 h. Crosslinking percentages of 2-layers and 3-layers prototype were 88.2 and 68.39, respectively. The swelling study showed a controlled swelling capability for 2-layers and 3-layers prototype, ∼5%. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay results showed good biocompatibility of 3-layers prototype and their suitability for preserving 48 h cell viability in 3D cultures. Moreover, a significant increment of absorbance value was measured after 48 h, demonstrating cell growth. Conclusions: Bioink obtained combining chitosan and poly-γ-glutamic acid represents a good option for 3D bioprinting. A stable 3D structure was realized by layer-by-layer deposition technology; compared with other papers, the present study succeeded in using medical healthcare-grade polymers, no-toxic crosslinker, and solvents according to ICH Topic Q3C (R4).